(untitled) (Symposium on Life and Environmental Sciences, 2026)
The Silk Road was one of the most important trade and cultural systems in world history, connecting the East and the West for centuries. This route was not only a space for economic relations - it also became the main axis of mutual influence of cultures, religions, technologies and civilizations. The geographical location of Georgia, which includes the transit space of the Black Sea and the Caucasus, gave the country an important strategic function.